The Thirst for Islamic Knowledge in the Digital Era - Mustafa, Esra Ahmed Abdulhalim (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
In this research, I attempt to investigate the new media as an alternative for acquiring ilmu Shari’i. The decline of the conventional way for many reasons, in addition to the revolutionary development of technology, has encouraged many people to follow up in a different way to acknowledge Islam and Islamic knowledge. I also argue that these online platforms help Muslim youth confirm their identity through their attraction to social media. I consider the case of Ahmed Al Sayed and his influence on Muslim youth in the Arab world. In this research, I analyze social media interaction among Muslim youth by using the qualitative research method. This study contributes to understanding the impact of the age of transformation in technology on youth seeking Islamic knowledge.